2022
DOI: 10.3389/fmicb.2022.988984
|View full text |Cite
|
Sign up to set email alerts
|

Differences in meat quality between Angus cattle and Xinjiang brown cattle in association with gut microbiota and its lipid metabolism

Abstract: Gut microbiota plays important roles in mediating fat metabolic events in humans and animals. However, the differences of meat quality traits related to the lipid metabolism (MQT-LM) in association with gut microbiota involving in lipid metabolism have not been well explored between Angus cattle (AG) and Xinjiang brown cattle (BC). Ten heads of 18-month-old uncastrated male AG and BC (5 in each group) raised under the identical conditions were selected to test MQT-LM, i.e., the backfat thickness (BFT), the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…In addition, the chemical state of myoglobin is a key factor that affects meat color ( Suman and Joseph, 2013 ). Chen et al (2022) revealed that L-aspartic acid was positively correlated with intramuscular fat concentrations, suggesting that this metabolite may determine meat quality. In practical application, aspartic acid and glutamine contribute to umami taste ( Nanda et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the chemical state of myoglobin is a key factor that affects meat color ( Suman and Joseph, 2013 ). Chen et al (2022) revealed that L-aspartic acid was positively correlated with intramuscular fat concentrations, suggesting that this metabolite may determine meat quality. In practical application, aspartic acid and glutamine contribute to umami taste ( Nanda et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study reported that the F/B ratio was higher in feces of feedlot-fed Angus cattle than that in grazing cattle [ 33 ], indicating that the lower gut microbiota may influence the meat quality of cattle. In a recent study using Angus and Xinjiang brown cattle, intramuscular fat content was positively correlated with fecal Prevotella copri , Blautia wexlerae , and Ruminococcus gnavus bacterial species, and backfat thickness was negatively correlated with fecal Blautia wexlerae [ 34 ]. The relative abundance of unclassified Mogibacteriaceae and Succiniclasticum in the hindgut had a positive linear relationship with intramuscular fat content in the multibreed Angus-Brahman herd [ 35 ].…”
Section: Recent Research On Lower Gut Microbiome Contributing To Meat...mentioning
confidence: 99%
“…Zhang et al [ 43 ] indicated there was a strong association between fat content and lipid (ether lipid, glycerol lipid and glycerophospholipid) and carbohydrate metabolism (carbohydrate digestion and absorption, sucrose and starch, and galactose) in black Tibetan sheep. Another recent study also revealed that intramuscular fat content was positively correlated with the metabolites including succinate, oxoglutaric acid, L-aspartic acid and L-glutamic acid, and negatively correlated with GABA, L-asparagine and fumaric acid and Prevotella copri , Blautia wexlerae , and Ruminococcus gnavus [ 34 ]. Backfat thickness was negatively correlated with the metabolites including succinate, L-aspartic acid and L-glutamic acid and positively correlated with GABA, L-asparagine and fumaric acid and Blautia wexlerae [ 34 ].…”
Section: Host and Microbial Metabolome Contribution To Beef Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…These reports emphasized the value of the gut microbiota in the regulation of muscle fibre characteristics and meat quality. With respect to the meat quality of cattle, most studies have focused on the association of the ruminal environment and its lipid metabolic function (Chen, Sun, et al., 2022 ; Krause et al., 2020 ; Zheng et al., 2022 ), and the potential link between the gut microbiota and muscle fibre properties has not been well explored.…”
Section: The Gut–muscle Axis Has Become Increasingly Fascinating Due ...mentioning
confidence: 99%